O vermelho da vida na escrita de Hilda Hilst - Ludmilla Zago Andrade (2011)
This thesis addresses the life present in the work of Hilda Hilst. For this crop, it uses the logic of biografema, a term coined by Roland Barthes. The text refers to three biografemas linking the living and writing in Hilda: The red of life, the father and the House of the Sun.